2008
DOI: 10.1196/annals.1419.005
|View full text |Cite
|
Sign up to set email alerts
|

Physiology, Ecology, Phylogeny, and Genomics of Microorganisms Capable of Syntrophic Metabolism

Abstract: Syntrophic metabolism is diverse in two respects: phylogenetically with microorganisms capable of syntrophic metabolism found in the Deltaproteobacteria and in the low G+C gram-positive bacteria, and metabolically given the wide variety of compounds that can be syntrophically metabolized. The latter includes saturated fatty acids, unsaturated fatty acids, alcohols, and hydrocarbons. Besides residing in freshwater and marine anoxic sediments and soils, microbes capable of syntrophic metabolism also have been ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
313
1
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 364 publications
(325 citation statements)
references
References 121 publications
(372 reference statements)
6
313
1
5
Order By: Relevance
“…The closest related cultured species of labeled clostridial sequences, C. beijerinckii and C. puniceum, can produce substantial amounts of H 2 in addition to butyrate, acetate, formate and butanol . Although H 2 is a trophic link to methanogenesis and acetogenesis (Drake et al, 2006Hedderich and Whitman, 2006;Liu and Whitman, 2008;McInerney et al, 2008), methanogens and acetogens are not metabolically significant in the earthworm gut (Karsten and Drake, 1995).…”
Section: Fermentative Processes and General Diversity In Gut Contentsmentioning
confidence: 99%
“…The closest related cultured species of labeled clostridial sequences, C. beijerinckii and C. puniceum, can produce substantial amounts of H 2 in addition to butyrate, acetate, formate and butanol . Although H 2 is a trophic link to methanogenesis and acetogenesis (Drake et al, 2006Hedderich and Whitman, 2006;Liu and Whitman, 2008;McInerney et al, 2008), methanogens and acetogens are not metabolically significant in the earthworm gut (Karsten and Drake, 1995).…”
Section: Fermentative Processes and General Diversity In Gut Contentsmentioning
confidence: 99%
“…Interspecies symbiosis based on nutrient exchange (syntrophy) is well known in the bacterial world. 43 Bacteria are also known to communicate using an interspecies quorum sensing factor AI-2 that induces synthesis of proteins that are useful for a community rather than a single cell, such as toxins or polymer hydrolases. 44 Uncultured bacteria, however, do not grow on rich synthetic media, and AI-2 has not been found to function as a growth-promoting factor, raising questions about the nature of unknown growth-promoting factors in microbial communities.…”
Section: Growth Factorsmentioning
confidence: 99%
“…This type of cooperative interaction is very widespread among both Bacteria and Archaea and is frequently based on the reciprocal exchange of certain metabolites (Schink, 2002;McInerney et al, 2008;Sieuwerts et al, 2008;Morris et al, 2013). For those cases, where the interaction partners have been studied in more detail, characteristic features such as the loss of essential biosynthetic functions (McInerney et al, 2007) or the formation of physical attachment structures (Ishii et al, 2005;Wanner et al, 2008) have been reported that may have arisen as specific adaptations to the symbiotic lifestyle.…”
Section: Introductionmentioning
confidence: 99%